INFLUENCE OF MODERN INFORMATION TECHNOLOGIES IS ON FORMING OF MORAL CULTURE OF FUTURE SPECIALISTS OF OIL AND GAS INDUSTRY - Пішак, О. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In this article influence of innovative technologies is analyzed on inner spiritual world of users and forming of moral culture future specialists of technical branch. The basic ways of co-operation are outlined man-technique-man and development of modern communications is forecast in the nearest future.